Answer: The explicit rule for the geometric sequence is:
an=(2/5) (5)^(n-1), for n=1, 2, 3, 4, ...
Solution:
a1=2/5
an=5 (an-1)
n=2→a2=5 (a2-1)= 5 (a1)= 5 (2/5)→a2= (2/5) (5)
n=3→a3= 5 (a3-1)= 5 (a2)= 5 [(2/5) (5)]=(2/5) (5)^(1+1)→ a3=(2/5) (5)^2
n=4→a4= 5 (a4-1)= 5 (a3)= 5 [(2/5) (5)^2]= (2/5) (5)^(2+1)→ a4=(2/5) (5)^3
a1=2/5=(2/5) (1)=(2/5) (5)^0→a1=(2/5) (5)^(1-1)
a2=(2/5) (5)=(2/5) (5)^1→a2=(2/5) (5)^(2-1)
a3=(2/5) (5)^2→a3=(2/5) (5)^(3-1)
a4=(2/5) (5)^3→a4=(2/5) (5)^(4-1)
Then:
an=(2/5) (5)^(n-1), for n=1, 2, 3, 4, ...